Soil Susceptibility to Macropore Flow Across a Desert‐Oasis Ecotone of the Hexi Corridor, Northwest China. Issue 2 (26th February 2018) - Zhang, Yongyong; Zhao, Wenzhi; He, Jianhua; Fu, Li
Abstract: Macropore flow not only provides a fast pathway for water and solute transport and increases the risks of water and nutrient loss but also enhances soil aeration and groundwater recharge. However, macropore flow characteristics in irrigated oasis soils subject to continuous crop cultivation are poorly understood. This study was to investigate the effect of continuous cultivation on soil properties and macropore flow and to quantify the changes in macropore flow characteristics in an old oasis field (>50 years of cultivation, OOF), young oasis field (20 years, YOF), and adjacent uncultivated sandy area (0 year, USL) in Northwest China. Triplicate soil samples were collected from each site to investigate soil properties. Dye tracer experiments with also three replicates were conducted at each site. The degree of macropore flow (i.e., parameters of macropore flow) was highest at the OOF, intermediate at the YOF, and minimal at the USL. The macropore flow fraction (i.e., fraction of total infiltration flows through macropore flow pathways) at the OOF was 3.4 times greater than at the USL. The heterogeneous infiltration pattern at the OOF was dominated by macropore flow, while funnel flow was predominant at the USL. Long‐term irrigation with silt‐laden river water has increased silt + clay contents of the oasis soils. Irrigation and high‐input crop cultivation also increased organic matter. These changes in soil properties contributed to the interaggregate voids formation. The conversion of native desert soils to irrigated croplands increases the degree of macropore flow, which might enhance groundwater recharge in the desert‐oasis ecotone. Key Points: Continuous cultivation with river water irrigation enhanced soil properties and the degree of preferential flow Preferential flow was dominated at old oasis field and young oasis field, while funnel flow was predominant at uncultivated sandy area Silt and clay content, soil organic carbon, and macroporosity had positive influence on preferential flow occurrence